Practice of Auditing within organizations: Diagnosis and peculiarities: Pratique d’Audit au sein des organisations : Diagnostic & particularités - El Bouzaidi, Dounia; Zenasni, Mourad (African Scientific Journal, 2021)
In the current competitive conditions, several structures aim to improve their performance and align with the best international standards. Improving performance therefore requires the establishment of a regular control system in order to continually challenge the functioning of the structure’s processes. This editorial contribution provides an overview of the various audits while explaining the characteristics and specificities of each. This diagnosis first of all differentiates internal audit (IA) and external audit (EA) and then presents the typologies classified by theme. A point will be particularly devoted to the importance of the Occupational Safety and Health (OSH) audit. This contribution presents, in the end, a consolidation of observations and recommendations on the basis of the documentation published on this subject. Résumé Dans les conditions de concurrence actuelles, plusieurs structures visent à faire évoluer leur performance et à s’aligner sur les meilleurs standards internationaux. L’amélioration de la performance nécessite ainsi l’instauration d’un dispositif de contrôle régulier afin de challenger continuellement le fonctionnement des processus de la structure. La présente contribution éditoriale dresse un état des lieux des différents audits tout en expliquant les caractéristiques et les spécificités de chacun. Ce diagnostic différencie tout d’abord l’audit interne (AI) et l’audit externe (AE) et présente, par la suite, les typologies classées par thématique. Un point sera particulièrement consacré à l’importance de l’audit Santé Sécurité au Travail (SST). Cette contribution présente, au final, une consolidation d’observations et de recommandations sur la base de la documentation publiée à ce sujet. Mots clés : typologie d’audit, normes, objectifs de certification, rôle et attributions des audits, différences et particularités et audit SST.